Antibiotic consumption and medication cost in diabetic patients: Insights from Iran health insurance organization (IHIO) claims data - Arash Bagherian Ghotbi; Benyamin Khoshparast; Hamidreza Hekmat; Zahra Shahali; Ali Golestani; Ozra Tabatabaei-Malazy (PLoS ONE, 2026)
Background The rising prevalence of diabetes is increasing the healthcare costs especially when associated with infection. We aimed to assess the antibiotic consumption and medication costs in diabetes. Methods We performed a retrospective claims-based study using Iranian Health Insurance Organization (IHIO) dataset from 24 provinces during 2014–2017. Systemic antibacterials were quantified in defined daily doses and diabetic patients were stratified into “No antibiotic” (NAb) and quartiles of cumulative antibiotic exposure (Q1–Q4). A dominant antidiabetic regimen was assigned when ≥80% of a patient’s diabetes prescriptions came from one drug class or combination. Inflation-adjusted annual medication costs were modelled with log-link Gamma generalized linear models. Results The study comprised 1,704,182 individuals (62.0% women). Biguanides alone were most common dominant diabetes regimen (40%), whereas penicillin accounted for 35.8% of all antibiotic dispensing. Mean annual medication costs were 93 USD for women and 138 USD for men; however, after adjustment men incurred slightly lower costs than women. Compared with the NAb group, costs rose progressively with antibiotic exposure, reaching an adjusted mean ratio (MR) 3.17 (95%CI 3.09–3.25) in Q4. Relative to biguanide monotherapy, costs were markedly higher for regimens biguanides + insulins (MR 5.75, 5.54–5.97) or insulins alone (MR 5.53, 5.38–5.68). Conclusion Quantifying the joint impact of antidiabetic regimens and antibiotic use on treatment costs highlights key factors driving healthcare expenditures. These findings can inform targeted antibiotic stewardship strategies and guide reimbursement policy to optimize resource allocation and reduce the financial burden on both patients and insurers.